PERKEMBANGAN PEMIKIRAN DAN PERGERAKAN WANITA DALAM PANDANGAN FEMINIS MUSLIM - Asfa Fikriah (UIN Mataram, 2018)
Islam is the religion of rahmatan lil-‘alamin which carries the main mission to realize the benefits and justice for humanity and all beings in the world. Islam provides rules that are fair to humans, especially for men and women, so that everyone benefits from the rules. With two main sources, the Qur'an and the Sunnah, Islam places men and women fairly and equally, even though there are different rules for both. However, the ulama's interpretation of the Qur'an and Sunnah based on culture led to the emergence of the determination (fiqh) of the women lost from the mission carried out by two sources. The emergence of feminist Muslim leaders with ideas of gender equality has a significant effect on the Muslim community to realize the injustices of men and women over the years, especially in Islam, and try to return to justice and gender equality.